1948
DOI: 10.1002/ar.1091010111
|View full text |Cite
|
Sign up to set email alerts
|

The innervation of the knee joint

Abstract: FOUR FIGUREStaining to this is of value since it allows a comparison with what is known regarding other animals. F o r example, it has been shown that in the knee joint of the mouse (Gardner, '42) and of the cat (Gardner, '44) there are regional differences in distribution and in types of nerve endings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
133
1
5

Year Published

1948
1948
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 8 publications
8
133
1
5
Order By: Relevance
“…It is already known that inflammation leads to angiogenesis and sensory nerve growth along new blood vessels in osteoarthritic joints [13]. In the immunohistochemical analysis, neovessels and accompanying nerve growth have been reported in synovium [14] and fat pads [15,16] of osteoarthritic joints. However, to our knowledge, nobody has clearly demonstrated that these sensory nerves along vessels play an important role in patients' symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that inflammation leads to angiogenesis and sensory nerve growth along new blood vessels in osteoarthritic joints [13]. In the immunohistochemical analysis, neovessels and accompanying nerve growth have been reported in synovium [14] and fat pads [15,16] of osteoarthritic joints. However, to our knowledge, nobody has clearly demonstrated that these sensory nerves along vessels play an important role in patients' symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, however, our understanding of the innervation of the posterior knee is relatively incomplete as it is based primarily on anatomical descriptions dating back to more than six decades ago. 46 Hence, designing trials to quantify the effect of SNB accurately when its distribution is not clearly delineated is difficult at best. Additionally, the combined innervation of the knee joint by both the femoral and sciatic nerves, and the overlap in their innervation of the anterolateral aspect of the knee, 46 further complicate accurate assessment.…”
Section: Discussionmentioning
confidence: 99%
“…46 Hence, designing trials to quantify the effect of SNB accurately when its distribution is not clearly delineated is difficult at best. Additionally, the combined innervation of the knee joint by both the femoral and sciatic nerves, and the overlap in their innervation of the anterolateral aspect of the knee, 46 further complicate accurate assessment. In fact, few studies 12 have conceived designs capable of reliably isolating pain transmitted by the femoral and sciatic nerves, which would permit accurate quantification of a block's analgesic effects on the individual nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The largest concentration of nerve fibres seen histologically in a synovial joint is found in those parts of the joint most subjected to mechanical change during movement (Gardner, 1948). In the costo-transverse joint this would be the rostral and caudal aspects of the joint capsule.…”
Section: Discussionmentioning
confidence: 99%